أثر تطبيقات Quizizz و Kahoot في عملية تعلم اللغة العربية لدى الطلبة الماليزيين في المرحلة الثانوية العليا - Azlan Shaiful Baharum; Muhammad Norfaiz Rozanif; Ahmad Adnin Husin (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia